-5x = x + 6(1-x)
-5x = x + 6(1) + 6(-x)
-5x = x + 6 -6x
-5x = x - 6x + 6
-5x = -5x + 6
-5x + 5x = 6
0 = 6 Not equal. No solution.
(2x-5)² = (2x-1)(2x+1) -10(2x-1)
(2x-5)(2x-5) = (2x-1)(2x+1) - 20x + 10
2x(2x-5)-5(2x-5) = 2x(2x+1)-1(2x+1) - 20x + 10
4x² - 10x -10x + 25 = 4x² + 2x - 2x -1 - 20x + 10
4x² - 20x + 25 = 4x² - 20x - 1 + 10
4x² - 20x + 25 = 4x² - 20x - 9
Not equal. No solution.
ANSWER: M(-9,-4) to M’(-5,2)
If (x,y) is to (x+4,y+6)
Then (-9,-4) is to (-9+4,-4+6)
Hence (-9,-4) is to M’(-5,2)
Hopefully it’s correct
Answer:
4.575
Step-by-step explanation:
365.085/79.8=4.575
Answer:
y-2=9(x+3)
Step-by-step explanation:
y-y1=m(x-x1)
y-2=9(x-(-3))
y-2=9(x+3)